قياس أثر تغير سعر الصرف على الاستقرار النقدي الليبي - الشلمانيد.سراج عيسى (Aljameai, 2024)
المستخلص: هدفت هذه الدراسة إلى قياس أثر تغير سعر الصرف على الاستقرار النقدي في ليبيا وذلك خلال الفترة الزمنية (1985 إلى 2022) باستخدام نموذج ARDL)) (Autoregressive Distributed Lag) بالاعتماد على سعر الصرف الحقيقي كمتغير مستقل والاستقرار النقدي المتغير التابع متمثلا في القاعدة النقدية والتضخم كمتغير ضابط، وتوصلت الدراسة إلى وجود أثر إيجابي لتغير سعر الصرف الحقيقي والتضخم على الاستقرار النقدي، وكذلك وجود علاقة تكامل مشترك بين متغير المستقل والمتغير التابع. Abstract: This study aimed to measure the impact of the exchange rate on changes monetary stability in Libya during the time period (1985 to 2022) using the Autoregressive Distributed Lag (ARDL) model based on the time series of the study variables. Exchange rate as indepenant variable and monetary stability as dependent variable represented by the monetary base and inflation as a control variable, The study concluded that there is a positive effect of the real exchange rate and inflation as control variable on the monetary base, as well as the existence of a co-integration relationship between the independent variable and the dependent variable.